Bioenergy and agriculture: Promises and challenges: Science and technology options for harnessing bioenergy's potential - Woods, Jeremy (International Food Policy Research Institute, 2006)
Much of the technology development for bioenergy to date has been geared toward competing with cheap fossil fuels. Bioenergy technologies have focused on reducing the cost per unit of energy produced, often exclusively by exploiting very cheap feedstocks and processing them on a large scale. But as the era of cheap fossil fuels comes to an end and as societies become more willing to pay for sustainable energy sources that reduce greenhouse gas emissions, there will be new opportunities for developing and using bioenergy technologies that can contribute to a wider range of economic, social, and environmental objectives. This brief discusses current and future technologies and options appropriate to developing countries.